The plethora of Tubeufiaceae in lakes of the northwestern Yunnan plateau, China - Li, Long-Li; Shen, Hong-Wei; Bao, Dan-Feng; Wanasinghe, Dhanushka N.; Lu, Yong-Zhong; Feng, Yuan; Luo, Zong-Long (Frontiers in Microbiology, 2022)
Diversity of lignicolous freshwater fungi in northwestern Yunnan, China is being studied for several years in College of Agronomy and Biosciences, Dali University. During last five years, we published 2 new genera, 9 new species of Tubeufiaceae from northwestern Yunnan. This study, focused to introduce tubeufia-like hyphomycetous fungi from the freshwater lakes in northwestern Yunnan plateau. Eleven fresh collections of tubeufiaceous taxa were collected and identified. Among of them, a new genus, Neomanoharachariella is introduced to accommodate Neomanoharachariella aquatica which is characterized by light brown to dark brown, dictyoseptate, broadly oval to ellipsoid and well-developed conidiophores. Two new species viz. Neohelicosporium suae and Parahelicomyces suae; two new records Helicoma rufum, Helicoma rugosum and two new collections Parahelicomyces hyalosporus, Tubeufia cylindrothecia are introduced based on morphological evidence and the results of molecular phylogenetic analysis of combined ITS, LSU, TEF1-α and RPB2 sequence data. The detailed descriptions and illustrations of these species are provided, as well as the morphological comparison with similar taxa are discussed.